EFEKTIVITAS UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA TERHADAP PENYELENGGARAAN PEMERINTAHAN DESA SABI SABILA KECEMATAN MOWEWE KABUPATEN KOLAKA TIMUR - La ode Dedihasriadi; Andi Novi Mudriani Djaoe (Institut Agama Islam Negeri (IAIN) Kendari, 2018)
The orientation of the implementation of regional autonomy is to improve public service and increase regional economy, contained three main missions, namely improve the quality and quantity public service to the society, create efficiency and effectiveness of the resources processing regions, and empower as well as creating the space for the community to participate in development. In connection the composition and regional government administration, after the amendment of constitution of the Republic of Indonesia year 1945, arrangement village or called any others name in terms of his reign reference to the article 18 paragraph (7) statethat “the composition and procedures of governance regulated in a law”. It meansthat article 18 paragraph (7) the constitution of the Republic of Indonesia year 1945 open the possibility of an arrangement in governance system of Indonesia. In the act of consideren was brought up Village has the rights of origin and traditional rights to regulate and manage the interests of the local community and as referred in the article 4 of the law which are to give recognition and respect for the existing Village with its diversity before and after the formation of the Republic of Indonesia